Forms of political union : a discussion paper on a union to suit our needs (OECS Secretariat CastriesLC, 1988)
Describes and explains the various forms of political union which characterise countries in the world viz. unitary state, confederation, federation and some related political concepts. Examines the implications for the Eastern Caribbean if one or the other form were implemented.
IDS